LEARNING PHYSICS PBL MODEL USING CONTEXTUAL APPROACHES TO IMPROVE STUDENT HIGHER ORDER THINKING SKILLS (HOTS) - EKA VIRDIYANTI, FEZYLIA; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2020)
Abstract Higher Order Thinking Skills (HOTs) are the thinking skills needed in the 21st century and in the era of the industrial revolution 4.0. This research aims to describe the effectiveness of the Problem Based Learning (PBL) model with a contextual approach to physics learning to improve students HOTs. This research is Pre Experimental by using pre-test and post-test design. The research sample was 86 students of class X state senior high school in Surabaya, Indonesia in the odd semester of the academic year 2019/2020. This research sample, divided into 3 (three) classes of the same experiment. Before learning physics using the PBL model with a contextual approach, all students in all three classes were given a first test (pre-test), and after the same study, all students in the three classes were again given a final test (post-test) with test material the same one. Data that has been collected is then analyzed using n-gain calculations, paired t-tests, and analysis of variance (Anova). The results showed that after applying physics learning using PBL models with a contextual approach, students HOTs scores increased significantly at alpha 5%, with average n-gain categorized as moderate, and consistent (not different) in all three experimental classes. So it can be concluded that learning physics using PBL models with an effective contextual approach can improve students? HOTs. Thus, to improve students? HOTs, PBL model learning can be used with a contextual approach. Keywords: PBL, Kontekstual, HOTs